2023
DOI: 10.1088/1741-2552/acb5c2
|View full text |Cite
|
Sign up to set email alerts
|

Decoding spatial locations from primate lateral prefrontal cortex neural activity during virtual navigation

Abstract: Objective. Decoding the intended trajectories from brain signals using a brain-computer interface system could be used to improve the mobility of patients with disabilities. Approach. Neuronal activity associated with spatial locations was examined while macaques performed a navigation task within a virtual environment. Main results. Here, we provide proof of principle that multi-unit spiking activity recorded from the lateral prefrontal cortex of non-human primates can be used to predict the location of a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Over half of these cells were also modulated by which side the monkey was looking at. Interestingly a recent study has reported that spatial position in the X‐maze can be decoded from neural population activity in the LPFC of macaque monkeys (Johnston et al, 2023). This suggests that LPFC neurons also encode view or spatial information that may be available during navigation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of these cells were also modulated by which side the monkey was looking at. Interestingly a recent study has reported that spatial position in the X‐maze can be decoded from neural population activity in the LPFC of macaque monkeys (Johnston et al, 2023). This suggests that LPFC neurons also encode view or spatial information that may be available during navigation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This capacity to execute actions that cause a change in the virtual world is referred to as a feeling of agency (Bódi, 2022). Other studies have used virtual environments as a surrogate for real-world naturalistic settings and reported tuning for spatial working memory in LPFC and for stimulus features in the hippocampus (Corrigan et al, 2022; Gulli et al, 2020; Johnston et al, 2023; Roussy et al, 2021; Wirth et al, 2017). This factor should not be underestimated since here animals do not act as passive observers but as actors, triggering task events.…”
Section: Discussionmentioning
confidence: 99%